Structural characterization of wild edible Pleurotuscollected from Punjab, India - KAUR, AMANPREET; SODHI, H S (The Indian Journal of Agricultural Sciences, 2024)
Oyster mushroom (Pleurotus spp.) belongs to the class Basidiomycetes, family Agaricaceae, commonly known as ‘dhingri’ in India and proliferates naturally on dead, decay wooden logs or trunks of deciduous or coniferous woods in tropical and temperate forests. Although Pleurotus mushrooms are commercially important mushrooms but wild Pleurotus still require public recognition. Hence, the present study aimed to conduct a field survey for collection of Pleurotus mushrooms from wild regions of of Punjab Two wild Pleurotus were collected and domesticated at Mushroom Research Complex, Punjab Agricultural University, Ludhiana, Punjab which were further analyzed at molecular and biochemical levels. These mushrooms were identified at species level through ITS (Internal transcribed spacer region) based method (18S ribosomal RNA gene, internal transcribed spacer, 5.8S ribosomal RNA gene, complete sequence; and 28S ribosomal RNA gene) was carried out. The gene bank accessioned Pleurotus sapidus as MK 281339 and Pleurotus floridanus as MK 281340. Hyphae of Pleurotus sapidus was observed to be packed tightly to a greater extent as compared to Pleurotus floridanus according to the ultra-structure recorded by scanning electron microscope. Both species of Pleurotus share two different proteins of same molecular weight 24.81 KDa and 28.43 KDa. Collecting and identifying wild species is crucial to preserve the wild fruits and fathom out the benefits of wild edible Pleurotus spp.